A method for producing battery grade lithium carbonate from spodumene

CN122940188APending Publication Date: 2026-10-20GANSU COMANDA ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312705.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,该工艺存在若干难以逾越的固有缺陷:其一,能耗高昂且相变效率受限

Benefits of technology

本发明提供了一种从锂辉石制备电池级碳酸锂的方法,包括下列步骤:将锂辉石精矿与钠盐活化剂混合,研磨后置于微波场中,辐照焙烧,得到焙烧熟料;将焙烧熟料依次进行梯度酸浸、净化处理、结晶沉淀、后处理,得到电池级碳酸锂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of efficient lithium resource extraction technology, and in particular to a method for preparing battery-grade lithium carbonate from spodumene. The method includes: mixing spodumene concentrate with a sodium salt activator, grinding the mixture, and then irradiating and roasting it in a microwave field to obtain roasted clinker; subjecting the roasted clinker to gradient acid leaching, purification, crystallization precipitation, and post-treatment to obtain battery-grade lithium carbonate. This invention achieves a deep synergy between mechanochemical activation pre-damage to the crystal lattice and low-temperature transformation via microwave field heating, reducing the roasting temperature to 800-850℃ and energy consumption by 30%-40%; gradient acid leaching, purification, and crystallization precipitation result in a lithium leaching rate >95%, and the final product, lithium carbonate, has a chemical purity ≥99.5%, sodium content <200ppm, and potassium content <50ppm; the particle size distribution is concentrated (D...). 90 / D 10 ≤2.0) and tap density ≥1.2g / cm³ 3 Its excellent physical properties make it suitable for the preparation of high-end lithium-ion battery cathode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of efficient lithium resource extraction technology, and in particular to a method for preparing battery-grade lithium carbonate from spodumene. Background Technology

[0002] Against the backdrop of a global strategic shift towards a cleaner and lower-carbon energy structure, lithium, as a core material in the new energy system, has received unprecedented strategic attention. Driven particularly by the explosive growth of the electric vehicle and large-scale energy storage markets, extremely stringent requirements have been placed on the yield and quality of battery-grade lithium carbonate. Spodumene (LiAlSi2O6), as the most important lithium-bearing hard rock mineral, has become a mainstay in ensuring the security of the global battery-grade lithium carbonate supply chain due to its wide distribution and high grade.

[0003] However, naturally occurring α-spodumene belongs to the monoclinic crystal system (space group C2 / c), and its lattice consists of [SiO4] tetrahedral single chains and [AlO6] octahedral chains connected by Li + The cross-linking forms an extremely dense "sandwich" three-dimensional framework structure. In this configuration, lithium ions are tightly locked within narrow six-membered ring channels (M2 sites), resulting in extremely high chemical inertness at room temperature. This extremely high chemical inertness, derived from the intrinsic density of the crystal lattice, is a thermodynamic barrier that urgently needs to be overcome in industrial lithium extraction metallurgy.

[0004] The current mainstream industrial process uses the traditional sulfuric acid process, which relies on high-temperature roasting (usually above 1050℃) to achieve the crystal transformation of α-spodumene into the relatively open β-spodumene, followed by acid leaching, purification, and precipitation to obtain lithium carbonate. However, this process has several inherent drawbacks: First, it is energy-intensive and has limited phase transformation efficiency. The high-temperature transformation roasting process above 1050℃ consumes a huge amount of energy, accounting for about 60% to 70% of the total energy consumption of the entire process. More seriously, the high temperature easily leads to local sintering on the material surface, forming a dense physical isolation layer that hinders the penetration of subsequent acid solutions, making it difficult to exceed the 90% upper limit of the actual lithium leaching rate, resulting in serious resource waste. Second, impurity separation is difficult, limiting product purity. In the subsequent chemical leaching treatment, impurity ions such as aluminum, iron, calcium, magnesium, and alkali metals (especially sodium and potassium) associated with the ore dissolve along with the lithium, forming an extremely complex solution system. Existing conventional purification technologies have very limited selective separation efficiency for alkali metal ions such as sodium and potassium, which have similar chemical properties to lithium. This has become a key bottleneck restricting the stable attainment of battery-grade purity (≥99.5%) in the final lithium carbonate product. Thirdly, the crystal morphology and physical properties are uncontrollable. Traditional precipitation processes often only focus on achieving chemical purity standards, lacking effective means to control the microscopic nucleation and growth kinetics of the product. The resulting lithium carbonate often exhibits irregular agglomeration, low tap density, and a wide particle size distribution. These physical defects directly impact the downstream cathode material preparation process, severely affecting the electrode's processing performance, tap density, and the final battery's energy density.

[0005] In summary, the further development of current spodumene lithium extraction processes is limited by interconnected technical bottlenecks such as high energy consumption from high-temperature roasting, difficulty in deep impurity removal, and uncontrollable physical properties of product crystallization. Therefore, there is an urgent need to develop an integrated process based on new principles that can synergistically work across multiple scales to achieve comprehensive improvements in key indicators such as energy consumption, yield, product purity, and physical properties in spodumene lithium extraction. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing battery-grade lithium carbonate from spodumene. By coupling multiple technologies, the phase transition process is changed from the reaction mechanism, thereby achieving low-temperature, high-efficiency, and highly selective lithium extraction and the preparation of high-quality battery-grade lithium carbonate.

[0007] To achieve the above objectives, the present invention provides a method for preparing battery-grade lithium carbonate from spodumene, comprising the following steps: Lithium spodumene concentrate was mixed with sodium salt activator, ground, and then placed in a microwave field for irradiation roasting to obtain roasted clinker. The roasted clinker was subjected to gradient acid leaching, purification, crystallization precipitation, and post-treatment in sequence to obtain battery-grade lithium carbonate.

[0008] In this invention, the sodium salt activator includes at least one of sodium carbonate and sodium hydroxide; the mass ratio of spodumene concentrate to sodium salt activator is 1:(0.9~1.1).

[0009] In this invention, the mixing process further includes adding a mineralizing agent, wherein the mass of the mineralizing agent accounts for 0.5% to 3% of the total mass of spodumene concentrate and sodium salt activator; the mineralizing agent includes at least one of calcium fluoride, sodium sulfate and sodium chloride.

[0010] In this invention, the grinding method is ball milling, the ball milling medium is zirconium oxide, the ball-to-material ratio is (10~15):1, the rotation speed is 400~500 r / min, and the time is 3~4 h.

[0011] The ball milling process pre-damages the crystal structure of spodumene concentrate at the atomic scale through high-intensity mechanical force, introducing a large number of lattice defects, increasing specific surface area and reactive sites. The aim is to weaken the Si-O-Al bonding network at the solid crystallographic level, thereby significantly reducing the thermodynamic activation energy barrier required for subsequent polymorphic phase transitions.

[0012] In this invention, the heating rate of the irradiation roasting is 10~20℃ / min, the target temperature is 800~850℃, and the holding time is 30~45min.

[0013] Irradiation roasting utilizes the bulk heating characteristics of microwaves and their selective heating advantage for polar substances / defect sites to achieve efficient and uniform heat transfer from the inside of the material to the outside. The synergistic effect of mechanical activation and microwave heating overturns the traditional high-temperature solid-state ion diffusion phase transition mechanism, successfully reducing the complete crystal transformation temperature of α-spodumene to active β-spodumene from above 1050℃ to the 800~850℃ range, and effectively suppressing the problems of material surface sintering and increased mass transfer resistance caused by traditional external conduction heating methods.

[0014] In this invention, the gradient acid leaching process includes: placing the calcined powder in a sulfuric acid solution with a concentration of 1.0~1.5 mol / L for a first-stage acid leaching, filtering to obtain a first leachate and a filter cake; placing the filter cake in a sulfuric acid solution with a concentration of 2.0~2.5 mol / L for a second-stage acid leaching, filtering to obtain a second leachate, and combining the first and second leachates to obtain a crude lithium sulfate solution; the temperature of the first-stage acid leaching is 70~80℃, the time is 20~40 min, and the solid-liquid mass ratio is (2.5~3.5):1; the temperature of the second-stage acid leaching is 95~98℃, the time is 60~100 min, and the solid-liquid mass ratio is (2.0~2.5):1.

[0015] In this invention, the purification process can be adjusted according to the composition of the spodumene concentrate. For example, when the Li₂O content in the spodumene concentrate is ≥6wt%, the purification process includes sequential primary impurity removal, secondary impurity removal, tertiary impurity removal, and precision filtration. The primary impurity removal process includes: heating the crude lithium sulfate solution obtained from gradient acid leaching to 75~85℃, adjusting the pH of the system to 4.5~5.0, stirring and aging for 25~35 minutes, and then pressure filtering to obtain the primary impurity-removed solution (which can effectively remove impurities after primary impurity removal). The secondary purification process includes: adding sodium fluoride or oxalic acid to the primary purification solution, adjusting the system temperature to 55-65℃, reacting for 40-50 minutes, filtering, and obtaining the secondary purification solution (which effectively removes calcium and magnesium ions after secondary purification); the tertiary purification process includes: passing the secondary purification solution into an ion exchange adsorption column at a flow rate of 1-3 BV / h to obtain the effluent; the ion exchange adsorption column is a manganese-based high-selectivity lithium-ion sieve or a titanium-based high-selectivity lithium-ion sieve (utilizing the high-selectivity lithium-ion sieve for Li... + The specific recognition and adsorption capabilities of the lithium sulfate effectively intercept sodium, potassium, and other alkali metal impurity ions that are extremely difficult to separate from the effluent. The precision filtration process includes: passing the effluent sequentially through a 1μm polypropylene filter element and a 0.22μm polyethersulfone microporous filter membrane to obtain a high-purity lithium sulfate solution.

[0016] When the Li₂O content in the spodumene concentrate is <6wt%, this type of spodumene concentrate often contains trace amounts of heavy metals. Therefore, the purification process includes sequential primary impurity removal, sulfidation to remove heavy metals, secondary impurity removal, tertiary impurity removal, and precision filtration. The steps of primary, secondary, and tertiary impurity removal and precision filtration are the same as those for spodumene concentrate with Li₂O content ≥6wt%. The sulfidation to remove heavy metals process includes adding a 10%~15% Na₂S solution to the primary impurity removal solution, where the amount of Na₂S added is 1.1~1.5 times the theoretical amount (the theoretical amount is the amount of Ca in the primary impurity removal solution). 2+ and Mg 2+ The total molar amount of heavy metal ions was stirred at 60-80℃ for 30-60 min, maintaining the pH of the system at 5.0-6.0 during the reaction to allow the heavy metal ions to precipitate as sulfides. After filtration, the heavy metal-free solution was obtained. After this step, inductively coupled plasma optical emission spectrometry (ICP-OES) was used to detect the residual concentrations of heavy metal ions such as copper, lead, and zinc in the solution, and the concentrations were all below 1 mg / L.

[0017] In this invention, the crystallization and precipitation process includes: mixing a purified high-purity lithium sulfate solution with a precipitant, and controlling the CO3 content in the mixture. 2- The molar amount is greater than that of Li +The molar amount of the precipitant is then used; a precipitation reaction is carried out at 55~65℃ to obtain a crystalline slurry; the pH of the system is maintained at 7.0~7.5 during the precipitation reaction; the precipitant includes sodium carbonate solution or carbon dioxide gas.

[0018] Preferably, during the crystallization and precipitation process, after the high-purity lithium sulfate solution is mixed with the precipitant, a crystal morphology guiding agent is added; the crystal morphology guiding agent includes at least one of sodium dodecyl sulfate and sodium carboxymethyl cellulose. The present invention does not impose a special limitation on the amount of the crystal morphology guiding agent; it can be adjusted according to the type of crystal morphology guiding agent. The crystal morphology guiding agent can guide the directional nucleation and ordered growth of lithium carbonate crystals within the metastable region, changing the traditional disordered agglomeration crystallization mode, and realizing the design and control of the particle size distribution and microstructure of the final product.

[0019] Preferably, the crystallization precipitation process is carried out in an intelligent crystallization reactor equipped with a precision online temperature and pH monitoring and feedback system. In one embodiment of the present invention, the crystallization precipitation process specifically includes: controlling the temperature of the reaction system at 55~65°C, adding a precipitant and a high-purity lithium sulfate solution in a co-current or reverse manner to carry out the precipitation reaction, and using an automatic feed control system to stabilize the pH value of the reaction process at 7.0~7.5 during the precipitation reaction.

[0020] In this invention, the post-processing includes sequential separation, washing, and drying. The separation is a solid-liquid separation; the washing involves multi-stage countercurrent rinsing with deionized water at temperatures above 60°C until no white precipitate (indicating SO42-) is formed in the washing solution when tested with a 1% BaCl2 solution. 2- (After the anions have been thoroughly washed away), to remove trace impurity ions adsorbed on the surface and trapped between crystals; the drying temperature is 100~120℃ and the time is 6~10h.

[0021] Preferably, the post-processing further includes heat treatment of the dried product after drying, wherein the heat treatment temperature is 200~400℃ and the time is 4 hours. Heat treatment can effectively eliminate internal lattice stress and significantly improve the crystallinity and tap density of the final product.

[0022] The present invention also provides battery-grade lithium carbonate prepared by the above-described method for preparing battery-grade lithium carbonate from spodumene.

[0023] The present invention has the following beneficial effects: This invention provides a method for preparing battery-grade lithium carbonate from spodumene, comprising the following steps: mixing spodumene concentrate with a sodium salt activator, grinding the mixture, and then placing it in a microwave field for irradiation roasting to obtain roasted clinker; subjecting the roasted clinker to gradient acid leaching, purification treatment, crystallization precipitation, and post-treatment in sequence to obtain battery-grade lithium carbonate.

[0024] This invention constructs a complete process technology system integrating physical activation, energy field enhancement, solution chemical purification and crystal engineering control. (1) By pre-damaging the spodumene crystal structure at the atomic scale through mechanochemical activation, the energy barrier of the subsequent solid-phase phase transition is reduced by 200~250kJ / mol, so that calcination can be completed efficiently in the low temperature range of 800~850℃, which reduces energy consumption compared with the traditional process (≥1050℃) (the energy consumption of the whole process is reduced by 30~40%). (2) The microwave field heating method ensures the uniformity and efficiency of heat transfer, reduces the physical encapsulation effect caused by high temperature material sintering, and lays a solid kinetic foundation for the subsequent ultra-high lithium leaching rate of more than 95%. (3) The purification treatment of this invention adopts the alkali metal deep removal technology based on high-selectivity lithium ion sieve, which solves the key technical problem that sodium, potassium and other homologous impurities in the product are difficult to separate and are easy to exceed the standard in the traditional process, and ensures that the final chemical purity of lithium carbonate is stable at ≥99.5%. (4) The thermodynamic-kinetic coupled controllable crystallization process gives the product physical properties (particle size distribution uniformity, tap density) the ability to be "designed and controlled on demand", enabling it to better meet the preparation needs of downstream high-end high-energy-density lithium-ion battery cathode materials and significantly improve the added value of the product.

[0025] The lithium carbonate prepared by the method provided by this invention has an absolute chemical purity of ≥99.5%, and its key trace impurity indicators are extremely excellent: sodium content is less than 200 ppm, potassium content is less than 50 ppm, and the product has a concentrated and uniform particle size distribution (D) imparted by the crystallization kinetic process. 90 / D 10 ≤2.0), its powder physical tap density is not less than 1.2 g / cm³. 3 .

[0026] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0027] Figure 1 This is a schematic flowchart of the method for preparing battery-grade lithium carbonate from spodumene provided by the present invention. Figure 2 This is the XRD pattern of the lithium carbonate product obtained in Example 1 of this invention; Figure 3 This is a chemical composition analysis diagram of the lithium carbonate product obtained in Example 1 of the present invention; Figure 4 This is a particle size distribution curve of the lithium carbonate product obtained in Example 1 of the present invention. Detailed Implementation

[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0029] Example 1 The chemical composition of spodumene concentrate is as follows: Li₂O 6.85wt%, SiO₂ 64.2wt%, Al₂O₃ 22.5wt%, Fe₂O₃ 0.8wt%, CaO 0.5wt%, Na₂O 0.3wt%, K₂O 0.2wt%, and the particle size is ≤74μm (200 mesh) after sieving.

[0030] This embodiment provides a method for preparing battery-grade lithium carbonate from spodumene, the steps of which are as follows: 1 kg of spodumene concentrate was mixed with 1 kg of sodium carbonate and 20 g of calcium fluoride in a three-dimensional mixer for 30 min. The mixture was then loaded into the zirconia grinding jar of a QM-3SP4 planetary ball mill, and zirconia grinding balls (diameter ratio: Φ10 mm: Φ5 mm = 1:3) were added, setting the ball-to-material ratio to 12:1. The mixture was ball-milled at 450 r / min for 3.5 h in air to obtain activated powder. The specific surface area of ​​the activated powder was determined using the nitrogen adsorption method (BET). The results showed that the specific surface area of ​​the activated powder was 0.5 m² / h from the raw material (spodumene concentrate). 2 / g significantly increased to 4.8m 2 / g; X-ray diffraction analysis of the activated powder showed that the characteristic peaks of α-spodumene were significantly broadened, indicating that the crystal lattice underwent significant distortion and defect proliferation, and the pre-activation was successfully achieved.

[0031] The activated powder was evenly spread on a porous mullite calcining plate with a layer thickness controlled at 3 cm. It was then pushed into a box-type industrial microwave muffle furnace with a rated power of 6 kW and a frequency of 2.45 GHz. The temperature was increased from room temperature to 850°C at a rate of 15°C / min, and held for 35 min for irradiation roasting. (During irradiation roasting, the center temperature of the material was monitored by a shielded S-type thermocouple inserted into the furnace sidewall and an infrared thermometer to ensure uniform temperature field). After the holding period, microwave emission was stopped, and the material was cooled to 150°C with the furnace before being removed to obtain roasted clinker. X-ray diffraction analysis of the roasted clinker showed that the characteristic peaks of α-spodumene completely disappeared, and only the characteristic diffraction peaks of β-spodumene (JCPDS No. 25-0497) remained. The calculated phase transformation rate was greater than 99.5%, achieving complete transformation at low temperature.

[0032] 800g of roasted clinker was weighed and placed in a 2L jacketed glass reactor with mechanical stirring. 2.4L of 1.2mol / L sulfuric acid solution (liquid-to-solid mass ratio 3:1) was added, and stirring was started (200r / min). The system temperature was maintained at 75±2℃ in a water bath for the first stage of acid leaching. After 30min, the mixture was vacuum filtered to obtain the first leachate and filter residue. The filter residue was transferred to the reactor, and 1.6L of 2.2mol / L sulfuric acid solution (liquid-to-solid mass ratio 2:1) was added. The second stage of acid leaching was carried out at 97±2℃. After 80min, the mixture was vacuum filtered to obtain the second leachate. The first and second leachates were combined to obtain a crude lithium sulfate solution. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to analyze the crude lithium sulfate solution, and the total lithium leaching rate was calculated to be as high as 96.5%.

[0033] The crude lithium sulfate solution was heated to 80℃, and 10wt% NaOH solution was added dropwise while stirring. The final pH was precisely controlled to 4.8 using a high-precision pH meter. The solution was then stirred and aged for 30 minutes to generate Al(OH)3 and Fe(OH)3 flocculation precipitates. After pressure filtration, the first-stage purified liquid (after aluminum and iron removal) was obtained. NaF solution was added to the first-stage purified liquid, the amount of NaF added being based on the amount of Ca in the first-stage purified liquid. 2+ and Mg 2+ 1.15 times the total molar amount (theoretical amount refers to the amount based on Ca) 2+ +2F - →CaF2↓ and Mg 2+ +2F -→MgF2↓ requires stoichiometric moles of NaF for complete precipitation), adjust the system temperature to 60℃, react for 45 min to generate CaF2 and MgF2 precipitates, and obtain a secondary impurity-removed solution after fine filtration. Adjust the system temperature to 60℃, react for 45 min to generate CaF2 and MgF2 precipitates, and obtain a secondary impurity-removed solution after fine filtration. Pass the secondary impurity-removed solution through a glass exchange column (Φ50mm×H500mm) equipped with a pretreated H-type manganese-based high-selectivity lithium-ion sieve (λ-MnO2) at a constant flow rate of 2 BV / h to obtain the effluent. Pass the effluent sequentially through a 1μm polypropylene filter and a 0.22μm polyethersulfone microporous filter membrane to obtain a clear and transparent high-purity lithium sulfate solution. ICP-OES analysis of the high-purity lithium sulfate solution showed that its key component indicators were extremely excellent: Li + 26.8 g / L, Na + 85mg / L, K + <5mg / L, Ca 2+ 2mg / L, Mg 2+ 3 mg / L.

[0034] Take 500 mL of the above high-purity lithium sulfate solution and place it in a 1 L fully jacketed glass intelligent crystallizing vessel, connecting it to a precision constant-temperature circulating water bath. Turn on the anchor-type stirrer, setting the speed to 300 r / min, and slowly preheat the solution to 60℃ and maintain the temperature. Prepare a 200 g / L battery-grade sodium carbonate solution (Na2CO3 content ≥99.5%) as a precipitant. Using two high-precision fluid metering pumps, mix the lithium solution and sodium carbonate solution at a stoichiometric ratio (CO3... 2- Li + The feed ratio was 1.02:1, and the feed was continuously injected into the crystallizer in a parallel, synchronous manner, with the total feeding time strictly controlled within 120 minutes. Throughout the precipitation process, the pH was monitored online using a pH composite electrode, and NaOH solution was added dropwise by an automatic titration control system to precisely maintain the pH value of the reaction system at 7.2 ± 0.1. After the feed was completed, the mixture was aged at 60°C for another 45 minutes to obtain the crystallized slurry.

[0035] The crystallized slurry was transferred to a Buchner funnel for vacuum filtration. The filter cake was washed with deionized water at 75°C using a multi-stage countercurrent rinsing method. Specifically, the filter cake was added to 75°C deionized water and stirred to fully disperse it, forming a uniform suspension. Vacuum filtration was then performed to separate the mother liquor from the filter cake. This process was repeated three times. The filtrate obtained from each wash was used as the pre-wash liquid for the next batch of filter cake, thus achieving cascaded utilization of water resources. After each wash, the washing liquid was tested with a 1% (w / w) BaCl2 solution. The solution was considered safe until no white precipitate formed after adding BaCl2 solution, indicating the presence of SO42-. 2-The anions have been thoroughly washed away. The washed high-purity filter cake is transferred to a vacuum drying oven and deep dried at 110°C for 8 hours to obtain battery-grade lithium carbonate.

[0036] The battery-grade lithium carbonate prepared in Example 1 was analyzed using X-ray diffraction, and the results are as follows: Figure 2 As shown, the XRD diffraction pattern of the product exhibits sharp characteristic diffraction peaks at 2θ = 20.3°, 21.3°, 23.1°, 30.6°, 31.3°, 36.9°, and 39.1°, which correspond one-to-one with the crystal planes (-110), (110), (-111), (002), (-112), (-211), and (-202) of the Li2CO3 standard card (JCPDS No. 22-1141), and no characteristic peaks of any impurity phases are present. The diffraction peaks are narrow and sharp, with a small half-width at half-maximum, indicating that the product has good crystallinity and a complete crystal structure.

[0037] According to the standard method of GB / T 11064-2022, the main components and impurity content of battery-grade lithium carbonate were accurately determined by ICP-OES. The results are as follows: Figure 3 As shown. The test results are: Li₂CO₃ content as high as 99.58%; key trace impurities: Na 180mg / kg, K <10mg / kg, Ca 8mg / kg, Mg 7mg / kg, Fe 3mg / kg, SO₄²⁻ 2- 85 mg / kg. All chemical properties are significantly superior to the current YS / T 582-2013 industry standard for battery-grade lithium carbonate.

[0038] Physical crystallization performance test: Particle size distribution was determined using a high-resolution laser particle size analyzer, and the results are as follows: Figure 4 As shown, Figure 4 Display D 50 It is 10.2 μm, D 90 / D 10 The narrow width of 1.8 indicates that the particle size distribution is extremely concentrated and uniform.

[0039] Its tap density, measured according to GB / T 5162-2022 standard, is as high as 1.32 g / cm³. 3 It demonstrates excellent potential in powder processing and electrode compaction.

[0040] Example 2 This embodiment provides a method for preparing battery-grade lithium carbonate from spodumene, which is basically the same as the steps in Example 1, except that 50 mg of sodium carboxymethyl cellulose (CMC) with a molecular weight of 250,000 is added during the crystallization and precipitation process.

[0041] According to the standard method of GB / T 11064-2022, the main components and impurity content of battery-grade lithium carbonate were accurately determined by ICP-OES. The test results showed that the main Li2CO3 content in the obtained lithium carbonate product remained above 99.5%, meeting the battery-grade standard.

[0042] In terms of crystallographic characteristics, the product morphology and powder properties underwent significant changes. The specific surface area, determined using the BET nitrogen adsorption method, increased from 0.8 m² in Example 1 without the addition of the directing agent. 2 / g increased to 2.5m 2 / g; Laser particle size analyzer results show that D 50 The particle size distribution decreased from 10.2 μm in Example 1 to 6.5 μm, resulting in a narrower particle size distribution (D). 90 / D 10 ≤1.6); tap density increased from 1.32 g / cm³ in Example 1. 3 Slightly decreased to 1.18 g / cm³ 3 Scanning electron microscopy (SEM) observations showed that the product crystals transformed from the regular rhombohedral structure of Example 1 into fine, plate-like or petal-like aggregates. The significant increase in specific surface area is beneficial for improving the solid-phase reaction activity and mixing uniformity during the cathode material preparation process, making it suitable for high-performance cathode material systems with special requirements for precursor activity.

[0043] This fully demonstrates that the controllable crystallization platform provided by this invention can sensitively and effectively intervene in nucleation kinetics through additives, thereby meeting the special requirements of certain high-performance cathode materials (requiring highly active interfaces or special filling behaviors) for customized lithium carbonate precursors.

[0044] Example 3 The chemical composition of spodumene concentrate is as follows: Li2O 5.2 wt%, SiO2 65.0 wt%, Al2O3 24.0 wt%, Fe2O3 1.5 wt%, CaO 0.8 wt%, MgO 0.4 wt%, Na2O 0.6 wt%, and other trace components totaling 0.5 wt%. The particle size is ensured to be ≤74μm (200 mesh) after sieving.

[0045] This embodiment provides a method for preparing battery-grade lithium carbonate from spodumene, the steps of which are as follows: 1 kg of spodumene concentrate was mixed with 1.05 kg of sodium carbonate and 30 g of sodium sulfate in a three-dimensional mixer for 30 min. The mixture was then loaded into the zirconia grinding jar of a QM-3SP4 planetary ball mill, and zirconia grinding balls (diameter ratio: Φ10 mm: Φ5 mm = 1:3) were added. The ball-to-material ratio was set to 12:1. The mixture was ball-milled at 450 r / min for 3.5 h in air atmosphere to obtain activated powder.

[0046] The activated powder was evenly spread on a porous mullite calcining plate, with a layer thickness controlled at 3 cm. It was then pushed into a box-type industrial microwave muffle furnace with a rated power of 6 kW and a frequency of 2.45 GHz. The temperature was increased from room temperature to 830°C at a rate of 15°C / min, and held for 45 minutes for irradiation roasting. (During irradiation roasting, the center temperature of the material was monitored in tandem with a shielded S-type thermocouple inserted into the furnace sidewall and an infrared thermometer to ensure uniform temperature distribution). After the holding period, microwave emission was stopped, and the material was cooled to 150°C with the furnace before being removed to obtain the roasted clinker.

[0047] Weigh 800g of roasted clinker and place it in a 2L jacketed glass reactor with mechanical stirring. Add 2.4L of 1.2mol / L sulfuric acid solution (liquid-solid mass ratio 3:1), start stirring (200r / min), and maintain the system temperature at 75±2℃ in a water bath for the first stage of acid leaching. After 30min, vacuum filter to obtain the first leachate and filter residue. Transfer the filter residue to the reactor and add 1.6L of 2.2mol / L sulfuric acid solution (liquid-solid mass ratio 2:1). Perform the second stage of acid leaching at 97±2℃. After 80min, vacuum filter to obtain the second leachate. Combine the first and second leachates to obtain a crude lithium sulfate solution.

[0048] The crude lithium sulfate solution was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES), and the total lithium leaching rate was found to be as high as 94.1%.

[0049] The crude lithium sulfate solution was heated to 80℃, and 10wt% NaOH solution was added dropwise while stirring. The final pH was precisely controlled to 4.8 using a high-precision pH meter. The solution was then stirred and aged for 30 minutes to generate Al(OH)3 and Fe(OH)3 flocculation precipitates. After pressure filtration, the first-stage purified liquid (after aluminum and iron removal) was obtained. A 15% Na2S solution was added to the first-stage purified liquid, with the amount of Na2S added adjusted according to the Cu content in the solution. 2+ Pb 2+ Zn 2+ The total molar amount of heavy metal ions is 1.5 times that of the theoretical amount (based on Me). 2+ +S 2- →MeS↓ requires the stoichiometric moles of Na2S for complete precipitation. The reaction mixture was stirred at 65℃ for 45 min, maintaining the pH at 5.0-6.0 during the reaction to allow heavy metal ions to precipitate as sulfides. After filtration, the heavy metal-removed solution was obtained. Following this step, ICP-OES analysis showed that the residual concentrations of copper, lead, and zinc ions in the solution were all below 1 mg / L. NaF solution was then added to the primary impurity removal solution, the amount of NaF added being based on the amount of Ca in the primary impurity removal solution. 2+ and Mg2+ 1.15 times the total molar amount (theoretical amount refers to the amount based on Ca) 2+ +2F - →CaF2↓ and Mg 2+ +2F - →The stoichiometric number of NaF required for complete precipitation of MgF2↓ is used to adjust the system temperature to 60℃ and react for 45 min to generate CaF2 and MgF2 precipitates. After fine filtration, a secondary impurity-removed solution is obtained. The secondary impurity-removed solution is passed through a glass exchange column (Φ50mm×H500mm) equipped with a pretreated H-type manganese-based high-selectivity lithium ion sieve (λ-MnO2) at a constant flow rate of 2 BV / h to obtain the effluent. The effluent is then passed sequentially through a 1μm polypropylene filter and a 0.22μm polyethersulfone microporous filter membrane to obtain a clear and transparent high-purity lithium sulfate solution.

[0050] Take 500 mL of the above high-purity lithium sulfate solution and place it in a 1 L fully jacketed glass intelligent crystallizing vessel, connecting it to a precision constant-temperature circulating water bath. Turn on the anchor-type stirrer, setting the speed to 300 r / min, and slowly preheat the solution to 60℃ and maintain the temperature. Prepare a 200 g / L battery-grade sodium carbonate solution (Na2CO3 content ≥99.5%) as a precipitant. Using two high-precision fluid metering pumps, mix the lithium solution and sodium carbonate solution at a stoichiometric ratio (CO3... 2- Li + A 1.02:1 ratio of NaOH solution was continuously and synchronously injected into the crystallizer, with the total feeding time strictly controlled within 120 minutes. Throughout the precipitation process, the pH was monitored online using a pH composite electrode, and a dilute NaOH solution was added dropwise by an automatic titration control system to precisely lock the pH value of the reaction system within a narrow metastable window of 7.2 ± 0.1. After the feeding was completed, the mixture was aged at 60°C for another 45 minutes to obtain the crystallized slurry.

[0051] The crystallized slurry was transferred to a Buchner funnel for vacuum filtration. The filter cake was washed countercurrently with 75°C deionized water using a "slurry-filtration" method until no white precipitate (indicating SO4) was formed in the washing liquid when tested with 1% BaCl2 solution. 2- (Anions have been thoroughly washed away). The washed high-purity filter cake was transferred to a vacuum drying oven and deeply dried at 110°C for 8 hours to obtain battery-grade lithium carbonate.

[0052] According to the standard method of GB / T 11064-2022, the main components and impurity content of battery-grade lithium carbonate were accurately determined by ICP-OES. The test results were as follows: the main component content of Li2CO3 was as high as 99.52%, the sodium content was 320 mg / kg, the potassium content was less than 10 mg / kg, and the content of metallic impurities such as calcium, magnesium, and iron, as well as sulfate, all met the standard limit requirements of GB / T 11064-2022 for battery-grade lithium carbonate.

[0053] This result strongly demonstrates that even when faced with inferior ores with extremely low grade and complex impurity background, the process of this invention, through flexible adaptation of system parameters and combination of purification modules, can still efficiently and selectively extract lithium resources and stably produce qualified battery-grade lithium carbonate products, demonstrating strong process anti-interference capabilities and broad industrial application value.

[0054] Comparative Example 1 (Traditional High-Temperature Solid-State Calcination Process) The chemical composition of spodumene concentrate is as follows: Li₂O 6.85wt%, SiO₂ 64.2wt%, Al₂O₃ 22.5wt%, Fe₂O₃ 0.8wt%, CaO 0.5wt%, Na₂O 0.3wt%, K₂O 0.2wt%, and the particle size is ≤74μm (200 mesh) after sieving.

[0055] 1.0 kg of spodumene concentrate was mixed with 1.0 kg of sodium carbonate and placed in a box-type resistance furnace for roasting at 1080℃ for 100 min. After roasting, the material exhibited severe localized high-temperature melting and large hard agglomerates, necessitating an additional crushing and ball milling process for further processing. Traditional acid leaching and purification: The clinker was leached using a traditional single-stage concentrated acid method (high-concentration sulfuric acid, high liquid-to-solid ratio, near-boiling-point high-temperature long-term boiling). Solution purification relied solely on traditional alkali pH adjustment to remove aluminum and iron, and single-stage carbonate precipitation to remove calcium. Traditional precipitation: A traditional intermittent direct precipitation method was used, rapidly pouring a high-concentration sodium carbonate solution into the hot crude lithium solution without precise control of pH and supersaturation during the precipitation process.

[0056] Comparative Analysis: Due to the dense physical encapsulation caused by severe high-temperature sintering, despite the use of large amounts of concentrated acid, the final lithium leaching rate only reached 88.7%, with a significant amount of lithium resources lost with the waste residue. Lacking core technology for deep alkali removal using ion sieves, the final product purity was only 99.18% (failing to meet battery-grade standards), and the fatal sodium impurity content reached as high as 1250 mg / kg. Furthermore, due to the uncontrollable precipitation process, the final product's tap density was only 0.92 g / cm³. 3 This comparative data, encompassing four dimensions—energy consumption, extraction yield, chemical purity, and physical properties—highlights the revolutionary advantages and irreplaceable nature of the integrated process technology of this invention.

[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing battery-grade lithium carbonate from spodumene, characterized in that, Includes the following steps: Lithium spodumene concentrate was mixed with sodium salt activator, ground, and then placed in a microwave field for irradiation roasting to obtain roasted clinker. The roasted clinker was subjected to gradient acid leaching, purification, crystallization precipitation, and post-treatment in sequence to obtain battery-grade lithium carbonate.

2. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The sodium salt activator includes at least one of sodium carbonate and sodium hydroxide; The mass ratio of spodumene concentrate to sodium salt activator is 1:(0.9~1.1).

3. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The mixing process also includes adding a mineralizing agent, wherein the mass of the mineralizing agent accounts for 0.5% to 3% of the total mass of spodumene concentrate and sodium salt activator; The mineralizing agent includes at least one of calcium fluoride, sodium sulfate, and sodium chloride.

4. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The grinding method is ball milling, the grinding medium is zirconium oxide, the ball-to-material ratio is (10~15):1, the rotation speed is 400~500 r / min, and the time is 3~4 h.

5. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The heating rate of the irradiation roasting is 10~20℃ / min, the target temperature is 800~850℃, and the holding time is 30~45min.

6. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The gradient acid leaching process includes: placing the calcined powder in a sulfuric acid solution with a concentration of 1.0~1.5 mol / L for a first-stage acid leaching, filtering to obtain a first leachate and a filter cake; placing the filter cake in a sulfuric acid solution with a concentration of 2.0~2.5 mol / L for a second-stage acid leaching, filtering to obtain a second leachate, and combining the first and second leachates to obtain a crude lithium sulfate solution; The first stage of acid leaching is carried out at a temperature of 70~80℃ for 20~40 min, with a solid-liquid mass ratio of (2.5~3.5):

1. The second stage of acid leaching is carried out at a temperature of 95~98℃ for 60~100 min, with a solid-liquid mass ratio of (2.0~2.5):

1.

7. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The purification process includes sequential primary impurity removal, secondary impurity removal, tertiary impurity removal, and precision filtration. The primary impurity removal process includes: heating the crude lithium sulfate solution obtained by gradient acid leaching to 75~85℃, adjusting the pH of the system to 4.5~5.0, stirring and aging for 25~35 minutes, and then filtering by pressure to obtain the primary impurity removal solution; The secondary impurity removal process includes: adding sodium fluoride or oxalic acid to the primary impurity removal solution, adjusting the system temperature to 55~65℃, reacting for 40~50 min, filtering, and obtaining the secondary impurity removal solution; The three-stage impurity removal process includes: passing the secondary impurity removal solution into an ion exchange adsorption column at a flow rate of 1~3 BV / h to obtain an effluent; the ion exchange adsorption column is a manganese-based high-selectivity lithium-ion sieve or a titanium-based high-selectivity lithium-ion sieve. The precision filtration process includes: sequentially passing the effluent through a 1μm polypropylene filter element and a 0.22μm polyethersulfone microporous filter membrane to obtain a high-purity lithium sulfate solution.

8. The method for preparing battery-grade lithium carbonate from spodumene according to claim 1, characterized in that, The crystallization and precipitation process includes: mixing a purified high-purity lithium sulfate solution with a precipitant, and controlling the CO3 concentration in the mixture. 2- The molar amount is greater than that of Li + The molar amount was determined; then a precipitation reaction was carried out at 55~65℃ to obtain a crystalline slurry; the pH of the system was maintained at 7.0~7.5 during the precipitation reaction; The precipitant includes sodium carbonate solution or carbon dioxide gas.

9. A method for preparing battery-grade lithium carbonate from spodumene according to claim 8, characterized in that, In the crystallization and precipitation process, after the high-purity lithium sulfate solution is mixed with the precipitant, a crystal morphology guiding agent is also added. The crystal morphology guiding agent includes at least one of sodium dodecyl sulfate and sodium carboxymethyl cellulose.

10. Battery-grade lithium carbonate prepared by the method for preparing battery-grade lithium carbonate from spodumene according to any one of claims 1 to 9.